Vegetation diversity of mangrove forest in Percut Village, Percut Sei Tuan District, North Sumatra - Edi Azwar; Yusri Feviani; Bertaulina Haloho; Mhd. Rafi'i Ma'arif Tarigan (Universitas Islam Negeri Sumatera Utara, 2025)
This study aimed to analyze the vegetation diversity of mangrove forest in Percut Village, Percut Sei Tuan District, North Sumatra. A quantitative descriptive method with a field survey approach was employed, using purposively selected stations representing natural mangroves (Station I), mangroves adjacent to fishponds (Station II), and mangroves near an ecotourism area (Station III). Data were collected using 5 × 5 m² plots with 10 m spacing, including species identification, abundance measurements, and physicochemical parameter assessments (temperature, salinity, soil pH, and substrate texture). Vegetation characteristics were analyzed using the Shannon–Wiener diversity index (H’), evenness index (E), and Simpson’s dominance index (D). Results showed that environmental parameters across stations remained within the optimal range for mangrove growth (temperature 18.6–19.7°C, salinity 16.5–19‰, and pH 7–8.5), though variations indicated differing levels of anthropogenic pressure. Eight true mangrove species were identified: Sonneratia alba, Bruguiera cylindrica, Nypa fruticans, Acanthus ilicifolius, Rhizophora apiculata, Avicennia marina, Rhizophora mucronata, and Xylocarpus granatum. Vegetation analysis revealed a strong dominance of Rhizophora apiculata and Bruguiera cylindrica, while Xylocarpus granatum and Rhizophora mucronata occurred in limited numbers. The Shannon–Wiener diversity index (H’ = 0.8442) indicated low diversity and uneven species distribution, suggesting community instability linked to anthropogenic disturbances. These findings highlight the ecological impacts of land conversion and tourism activities on mangrove ecosystems and emphasize the need for conservation and rehabilitation efforts to maintain biodiversity and ecosystem services in the Percut Mangrove Forest.